DETERMINANTS OF SAVINGS HABIT AMONG CLIENTS OF BONZALI RURAL BANK IN THE TOLON-KUMBUNGU DISTRICT OF GHANA - Anang, B. T.; Dawuda, I.; Imoro, L. (UDS International Journal of Development, 2016)
The savings rate in a country is an important indicator of growth in the economy. However, savings remain very low in most developing countries where poverty, high unemployment rates and other factors seem to suppress the propensity to save. Policy-makers and researchers have therefore recognised the need to spur savings mobilisation in developing countries with very low savings rate. This study was therefore carried out to investigate the factors influencing savings habit of clients of the Bonzali Rural Bank in the Tolon-Kumbungu District of the Northern Ghana using cross-sectional data from 97 randomly selected respondents. Savings habit was analysed using probit regression. The study revealed that 32% of the respondents had got savings while 61% saved an amount not exceeding GHÂ¢500.00 per annum indicating that majority of the respondents were micro-savers. The following were identified as the factors influencing the decision to save: age, gender and marital status of the respondent. Income level and educational status were however not significant in determining savings habit. The authors recommend that to stimulate rural savings mobilisation, there is the need to target women who according to this study tend to save more. Â Keywords: Binary probit model, Northern Ghana, Savings habit